Talent management in emerging markets - Bluen, S. D. (Knowres Publishing, 2013)
While much has been written on talent management in the global context, talent management in emerging markets and the unique challenges and opportunities it presents has received little attention in the literature. This book explores these issues through theory, practice and case studies with contributions from scholars and practitioners based both in emerging markets and in Canada, the United Kingdom and The United States. The book provides the reader with a guide to setting up a talent management function in a multinational operating in emerging markets, including some 70 learnings and a set of key performance indicators with indicative targets to achieve when managing talent effectively in emerging markets. Throughout the book, talent management examples are drawn from diverse emerging markets across Asia (especially India and China), Africa, Central and Eastern Europe, the Middle East, and South America. These diverse examples underline the fact that, while we speak of 'emerging markets' as a single term, managing talent in each emerging country has unique features that need to be approached in a specific (rather than generic, one-size-fits-all) manner. The book is edited by Prof Steve Bluen. Contributors include; Dr Lyal White, Glynnis Rengger, Dr Mark Bussin, Richard Forbes, Prof. Theo Veldsman, Tony van Kralingen, Lara Hirschowitz, Italia Boninelli, Tamra Veley, Rob Mallick, Marcelo Williams, Jennifer Morris, and Prof Shirley Zinn. Case studies include: SABMiller Unilever Brazil Standard Bank Anglogold Ashanti Pick n Pay BAT Prof Steve Bluen, HR Consultant and Professor, Gordon Institute of Business Science and Former HR Executive, South African Breweries.